2005
DOI: 10.1161/01.hyp.0000185189.46698.15
|View full text |Cite|
|
Sign up to set email alerts
|

Nicorandil Promotes Myocardial Capillary and Arteriolar Growth in the Failing Heart of Dahl Salt-Sensitive Hypertensive Rats

Abstract: Abstract-Long-term administration of vasodilators increases shear stress, which is thought to be important for vascular growth in the heart. Nicorandil, an activator of ATP-sensitive potassium channels with a nitrate-like action, is a potent vasodilator. We have now investigated the effects of nicorandil on vascular growth and gene expression in the failing heart of Dahl salt-sensitive (DS) hypertensive rats. DS rats fed a high-salt diet from 6 weeks of age develop concentric cardiac hypertrophy secondary to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 42 publications
4
46
2
1
Order By: Relevance
“…Previous reports showed that the acute effect of nicorandil was assessed in low dose by gastric gavage: 6 mg/ kg, twice daily, for the heart failure model (23,24) or 3 mg/kg for the anti-gastric ulcer effect in fasted 6. The effects of nicorandil on blood pressure in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the acute effect of nicorandil was assessed in low dose by gastric gavage: 6 mg/ kg, twice daily, for the heart failure model (23,24) or 3 mg/kg for the anti-gastric ulcer effect in fasted 6. The effects of nicorandil on blood pressure in rats.…”
Section: Discussionmentioning
confidence: 99%
“…26 The advantages of NOG mice are that they show higher rates of engraftment of human HSCs and of myeloid/lymphoid reconstitution after transplantation of CBCD34 þ cells. [26][27][28][29][30] Before transplantation, we did not use DNA-damaging agents or radiation, which increase the production of chemokines and potentially expand the niche for HSCs and leukemia cells. In the early phase of 'primary leukemia cells' transplantation, we observed human leukemia cells not only on the surface of osteoblasts but also in the region adhering to vascular endothelia within a few days after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify if the sites of survival of human leukemia cells in the BM after chemotherapy are related to vascular region, dual immunohistochemistry was also performed combining anti-CD45 monoclonal antibody (Dako, Tokyo, Japan) with anti-tissue transglutaminase antibody (CUB 742; Dako, Tokyo, Japan). 27 Reactivity for CD45 was detected using the Ventanaenhanced alkaline phosphatase red detection kit. After washing in phosphate-buffered saline (pH 7.5) three times, staining for tissue transglutaminase was performed using a streptavidin biotin peroxidase linking system and diaminobenzidine as the chromogen with counterstaining.…”
Section: Pathological Examinationmentioning
confidence: 99%
“…Colitis was induced by application of TNBS in five groups, while the resting group was considered as sham group that received normal saline instead of TNBS. The five groups receiving TNBS were: 1-control group that received no treatment, 2-nicorandiltreated group (Nic) receiving nicorandil (6 mg/kg), a dose at which it does not show any antihypertensive effect [28], 3-glibenclamide-treated group (Glib) receiving glibenclamide (3 mg/kg) administered as a pure KATP channel blocker (PCB) in order to determine if nicorandil serves its possible effects through KATP channels, 4-nicorandil plus glibenclamide-treated group (Nic+Glib), in which nicorandil was administered 30 minutes after administration of glibenclamide [29], and 4-dexamethasone-treated group (Dexa) receiving dexamethasone (1 mg/kg) [30]. All the medications were prepared in a volume of 0.4 ml/ 200 g of body weight and administered by gavage for 7 days; the day of induction of colitis was considered as day 1.…”
Section: Experimental Designmentioning
confidence: 99%